Remote sensing mission sentinel pro: Analysis of satellite tracking, control, and health monitoring system with solar tracking capability - Baig Muhammad W.; Shafik Mahmoud (MATEC Web of Conferences, 2024)
Nowadays, satellite systems are experiencing noticeable disruptive issues due to the single functionality, high cost of operations, and limited adaptability. This paper presents a satellite mission control system with RF duplex communication, which gives multiple functionalities and health monitoring systems with solar tracking capability. This aims to present a flexible and affordable solution called the Remote Sensing Mission Sentinel Pro Platform. The quantitative approach is used and implemented to trans-receive data from space and pass it to the ground station. Arduino-based prototype uses the nRF24L01 module with an antenna at the ground station to trans-receive satellite data has been developed. Testing and verifications of the developed platform prototype indicated that satellites could monitor key health parameters, including temperature, humidity, and battery charge capacity.